2018
DOI: 10.1002/smll.201803291
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Hierarchical Hybrid Nanostructures from Fullerene‐Dendrons and Pyrene‐Dendrons

Abstract: The construction of fullerene (C60) hierarchical nanostructures with the help of amphiphilic molecules remains a challenging task in nanoscience and nanotechnology. Utilizing the host–guest complex concept, sub‐10 nm layered superstructures are constructed from a monofunctionalized C60 dendron (C60D, guest) and tweezer‐like pyrene dendron (PD, host). Since C60D and PD are asymmetric shape amphiphiles having liquid crystal (LC) dendrons, both C60D and PD construct head‐to‐head bilayer superstructures by themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…According to this roughly constructed HA morphology, the host LC molecules can overcome surface anchoring and align perpendicular to the surface direction. Given the fact that C 60 D has a layer packing structure (bilayer: 7.5 nm; monolayer: 3.75 nm) consisting of a tilted building block, it is demonstrated that the majority of partially constructed protrusions consist of monolayers of C 60 D molecules, while a small number of protrusions, measuring over 4 nm, exhibit an anomalous bilayer or trilayer structure (Figure a) . The mesogen segments would be heading to the host LC medium due to LC affinity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this roughly constructed HA morphology, the host LC molecules can overcome surface anchoring and align perpendicular to the surface direction. Given the fact that C 60 D has a layer packing structure (bilayer: 7.5 nm; monolayer: 3.75 nm) consisting of a tilted building block, it is demonstrated that the majority of partially constructed protrusions consist of monolayers of C 60 D molecules, while a small number of protrusions, measuring over 4 nm, exhibit an anomalous bilayer or trilayer structure (Figure a) . The mesogen segments would be heading to the host LC medium due to LC affinity .…”
Section: Resultsmentioning
confidence: 99%
“…The C 60 D molecule was synthesized according to a previous method . The nematic liquid crystal (NLC, ZSM-7232XX, LIXON ( T ni = 75 °C, Δε = −3.4, Δ n = 0.101)), anhydrous chloroform (99%, Sigma-Aldrich), acetone (99.5%, Showa), absolute ethanol (99.5%, Sigma-Aldrich), isopropyl alcohol (99.5%, Showa), and n -hexane (99.5%, Showa) were purchased and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Its band gap is 2.21 eV (Supporting information,F igure S3), indicating the presence of large p-conjugated system in the film. [8] Signals corresponding to Br andBcan be hardly observed, demonstrating the high conversion of the Suzuki polymerization (Figure 3d). The highresolution (HR) XPS spectrumo fC1s reveals am ajor peak of Csp 2 at 284.0 eV,w hereas other peaks ascribable to CÀO, C=O are quite weak (Figure 3d,i nset), in accordance with its highly aromatic structure.…”
mentioning
confidence: 98%
“…MMal and MFu molecules exhibited a typical layer structure with dspacings of 1.87, 1.25, 0.74, and 0.64 nm indexed as (002), (003), (005), and (006) for MMal and d-spacings of 1.72, 1.14, 0.83, 0.67, and 0.58 nm assigned as (002), (003), (004), (005), and (006) for MFu. 27 Presumably, the (001) diffraction is not observed due to overlap with the incident beam peak. Considering the calculated length (l MMal ≈ 3.8 nm, l MFu ≈ 4.5 nm) of a molecular long axis (Figure S5), MMal monomer is expected to possess a smectic A-like structure with the observed layer spacing (L MMal ) of 3.74 nm.…”
mentioning
confidence: 99%
“…To investigate the molecular packing structure of the mesogenic derivatives, one-dimensional (1D) wide-angle X-ray diffraction (WAXD) patterns were determined before and after thermal annealing at 90 °C for 10 min (Figure b). MMal and MFu molecules exhibited a typical layer structure with d -spacings of 1.87, 1.25, 0.74, and 0.64 nm indexed as (002), (003), (005), and (006) for MMal and d -spacings of 1.72, 1.14, 0.83, 0.67, and 0.58 nm assigned as (002), (003), (004), (005), and (006) for MFu . Presumably, the (001) diffraction is not observed due to overlap with the incident beam peak.…”
mentioning
confidence: 99%